Criminal victimization in higher education: college students as crime victims - Reyns, Bradford W. (Carolina Academic Press, 2020)
"This book offers a look inside the world of college student criminal victimization. Throughout this book we discuss all aspects of college student victimization, including why they may be victimized, what types of crimes they experience, how often they are victimized, and the consequences of that victimization. In addition, we detail the role of colleges and universities in helping to prevent and recover from victimization. Finally, we note possible programs and strategies that could help colleges and universities better address victimization on their campuses"--